GENOMIC DATA SECURITY AND PRIVACY IN HEALTHCARE INFORMATICS - Viswaketan Reddy Prodduturi (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The protection of genomic data in healthcare informatics presents unique challenges due to its highly sensitive and immutable nature. The article examines current cryptographic techniques, blockchain implementations, and regulatory compliance frameworks in genomic data security. With healthcare data breaches increasing by 55.1% annually and the average cost reaching 9.2 million per incident, robust security measures are crucial. The article analyzes modern encryption methodologies achieving 99.97% data utility while maintaining re-identification risk below 0.01%, and explores blockchain solutions that have demonstrated 99.99% uptime in genomic data sharing networks.